Initial insights on the biodiversity potential of biosolar roofs: a London Olympic Park green roof case study. Issue 1 (29th August 2016) - Nash, C.; Clough, J.; Gedge, D.; Lindsay, R.; Newport, D.; Ciupala, M.A.; Connop, S.
Abstract : Cities dominated by impervious artificial surfaces can experience a multitude of negative environmental impacts. Restoration of green infrastructure has been identified as a mechanism for increasing urban resilience, enabling cities to transition towards sustainable futures in the face of climate-driven change. Building rooftops represent a viable space for integrating new green infrastructure into high-density urban areas. Urban rooftops also provide prime locations for photovoltaic (PV) systems. There is an increasing recognition that these two technologies can be combined to deliver reciprocal benefits in terms of energy efficiency and biodiversity targets. Scarcity of scientific evaluation of the interaction between PVs and green roofs means that the potential benefits are currently poorly understood. This study documents evidence from a biodiversity monitoring study of a substantial biosolar roof installed in the Queen Elizabeth Olympic Park. Vegetation and invertebrate communities were sampled and habitat structure measured in relation to habitat niches on the roof, including PV panels. Ninety-two plant species were recorded on the roof and variation in vegetation structure associated with proximity to PV panels was identified. Almost 50% of target invertebrate species collected were designated of conservation importance. Arthropod distribution varied in relation to habitat niches on the roof. The overall aim of the Main Press Centre building green roof design was to create a mosaic of habitats to enhance biodiversity, and the results of the study suggest that PV panels can contribute to niche diversity on a green roof. Further detailed study is required to fully characterise the effects of PV panel density on biodiversity.